Note—A Note on the Optimality of the Modified Generalized Goal Decomposition Model - Davis, Wayne J.; Whitford, David T. (Management Science, 1985)
This note demonstrates that Freeland's (Freeland, J. R. 1976. A note on goal decomposition in a decentralized organization. Management Sci. 23 100–102.) modification of Ruefli's (Ruefli, T. W. 1971. A generalized goal decomposition model. Management Sci. 17 505–518.) Generalized Goal Decomposition model can generate nonoptimal solutions and shows how these difficulties can be corrected. In several papers on multi-level planning, it has been suggested that extending the hierarchical levels of the models from two to three or more levels is a straightforward process. This paper shows that this assertion is generally not true. The note points out that in Freeland's (Freeland, J. R. 1976. A note on goal decomposition in a decentralized organization. Management Sci. 23 100–102.) three-level model, the interactions between the two lowest level of the hierarchy must be strictly controlled before information is passed to the highest level of the organization.